Pengaruh Kompetensi, Iklim Sekolah dan Motivasi Kerja Terhadap Kinerja Guru Pada SMP Se-Kecamatan Pinang - Gemasih Ganti Nireta (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2023)
This study aims to determine: (1) the effect of competence on teacher performance; (2) the influence of school climate on teacher performance; (3) the effect of work motivation on teacher performance; and (4) the effect of principal leadership, school climate, and work motivation together on teacher performance. The research subjects were junior high school teachers in Pining District with a total sample of 110 people. The research method is a correlational quantitative research method with three independent variables and one dependent variable. Based on hypothesis testing, it can be concluded that there is a positive and significant effect between: (1) the principal's leadership on teacher performance of 0.412; (2) school climate on teacher performance is 0.403; (3) work motivation on teacher performance is 0.428; and (4) the principal's leadership, school climate, and work motivation together on teacher performance are 0.635. Overall, the results of the study show that teacher performance improvement can be done through an increase in the variables of the principal's leadership, school climate, and work motivation by 40.3% and the rest is determined by other variables.